A new family of [CuIILnIIIMV] heterotrimetallic complexes (Ln = La, Gd, Tb; M = Mo, W): model systems to probe exchange interactions and single-molecule magnet properties. Issue 18 (7th April 2016) - Visinescu, Diana; Alexandru, Maria-Gabriela; Madalan, Augustin M.; Jeon, Ie-Rang; Mathonière, Corine; Clérac, Rodolphe; Andruh, Marius
Abstract : Four 3d–4f–4(5)d heterotrimetallic complexes, [L 2 CuLn(H2 O)5 (μ -NC)M(CN)7 ], were obtained from the association of the binuclear 3d–4f complexes and {M V (CN)8 } 3− metalloligands. Abstract : Four isostructural trinuclear 3d–4f–4(5)d heterotrimetallic complexes, with the general formula [L 2 CuLn(H2 O)5 (μ-NC)M(CN)7 ], were obtained from the association of binuclear 3d–4f complexes and {M V (CN)8 } 3− metalloligands (M = Mo, Ln = La1 ; M = W, Ln = La2 ; M = Mo, Ln = Gd3 ; M = Mo; Ln = Tb4, where H2 L 2 = 1, 2-ethanediylbis(2-iminomethylene-6-methoxy-phenol)). The metalloligand coordinates through a single-cyanido group at the apical position of the copper(ii ) ion belonging to the Cu II Ln III binuclear complex. The analysis of the magnetic data for the La(iii ) derivatives (compounds1 and2 ), in the 1.85–300 K temperature range, shows a weak ferromagnetic exchange interaction between Cu II and Mo V /W V ions across the cyanido bridge ( J CuM / k B = 3.6(6) K; g = 2.23(5) for1 and J CuM / k B = 3.8(6) K, g = 2.21(5) for2, with H = −2 J CuM S Cu · S M ). These results were used to simulate the magnetic properties of compound3, using the isotropic spin Hamiltonian H = −2 J CuMo S Cu · S Mo − 2 J CuGd S Cu · S Gd . The resulting magnetic interaction between Cu II and Gd III ions via the phenoxo-bridge was found to be weakly ferromagnetic ( J CuGd / k B = +4.5(2) K with J CuMo / k B = +3.6(2) K, g Gd = g Cu = 2.00 and g Mo = 1.98). The dc magnetic properties for compound4 also show a predominant ferromagnetic interaction, while the ac magnetic measurements indicate the presence of the slow relaxation of the magnetization below 3.5 K.